2008
DOI: 10.3354/esr00103
|View full text |Cite
|
Sign up to set email alerts
|

Overfishing and the disappearance of short-beaked common dolphins from western Greece

Abstract: Once one of the most common cetaceans in the Mediterranean Sea, the short-beaked common dolphin has declined throughout the region since the 1960s and in 2003 this population was classified as Endangered in the International Union for Conservation of Nature (IUCN) Red List. Here, we document the species' precipitous decline in eastern Ionian Sea coastal waters across 13 yr. While 150 animals were present in the study area (1050 km 2) in 1996, only 15 were observed in 2007. A 12 mo assessment of fishing effort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 39 publications
(23 reference statements)
0
113
1
2
Order By: Relevance
“…About 150 common dolphins were present in 1996, but after 10 years of gradual population shrinking, only 15 animals had remained in 2007 (Bearzi et al, 2008). Bearzi et al (2008) carried out a subsequent assessment of fishing effort and catch and suggested that the decline was largely caused by prey depletion due to overfishing, especially by local purse seiners and beach seiners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 150 common dolphins were present in 1996, but after 10 years of gradual population shrinking, only 15 animals had remained in 2007 (Bearzi et al, 2008). Bearzi et al (2008) carried out a subsequent assessment of fishing effort and catch and suggested that the decline was largely caused by prey depletion due to overfishing, especially by local purse seiners and beach seiners.…”
Section: Discussionmentioning
confidence: 99%
“…3). Until 2003, this population covered the entire area, north of the line between the south-western part of Lefkada Island and the southern part of Kastos Island; however, after a dramatic decline, the few individuals left seem to have limited their range to the southern part of Lefkada Island (Bearzi et al, 2008). Very recent data indicate that the remaining individuals of this species may still be trying to expand their presence to their previous range (Tethys Research Institute, unpublished data).…”
Section: Ecosystem and Socioeconomic Componentsmentioning
confidence: 99%
“…For example, in the eastern Ionian Sea, the rapid decline of short-beaked common dolphins Delphinus delphis has been caused in major part by resource overlap between dolphins and purse-seine fisheries (Bearzi et al 2006(Bearzi et al , 2008. Fisheries on the Taiwanese west coast are unlikely to target dolphin prey species directly, because these species (e.g.…”
Section: Depletion Of Prey Resourcesmentioning
confidence: 99%
“…The species has to cope with a number of threats arising from human-induced impacts (FORCADA & HAMMOND 1998;TUDELA et al 2005;BEARZI et al 2010) including habitat deterioration, bioaccumulation of pollutants (BORRELL et al 2001;ZHOU et al 2001) and the effects of climate change (BRERETON et al 2010). This situation is more evident in the Mediterranean Sea, where the subpopulation was recently listed as endangered under the 2003 International Union for Conservation of Nature (IUCN) Red List of Threatened Species (BEARZI 2003), as demographic studies demonstrated a strong decline in the population, particularly in the eastern basin (BEARZI et al 2008). The most important remaining habitat for the Mediterranean subpopulation is located in the Alboran Sea, in the western basin (CANÃDAS & HAMMOND 2008).…”
Section: Introductionmentioning
confidence: 99%